Considering Essays: The Social Construction of Subcultural Value - Grills, Scott (Qualitative Sociology Review, 2017)
The article examines the social processes that accompany the social construction of value within subcultural settings. Taking the evaluation of university essays as the case-at-hand, this paper argues for the importance of attending to the generic social process of assigning evaluative meaning. Specifically, this article locates these processes relative to the themes of: 1) socialization of new academics, 2) contextualizing the essay pedagogically and pragmatically, 3) grades as currency, 4) recipes of action and meaning-making, 5) assigning grades, and 6) managing troublesome cases. The collective work that we do to rank, sort, evaluate, and determine the relative worth of social objects reflects a set of processes that are to be found in multiple settings. This article contributes to our understanding of these rather central everyday life activities.